Explore the Potential for Tourist Scams in Indonesia - TARJO, Tarjo; ANGGONO, Alexander; SAKTI, Eklamsia; ZAKIK, Zakik; SYARIF, Muh; SAFKAUR, Otniel; SAID, Jamaliah (Journal of Environmental Management and Tourism, 2023)
This study aims to explore the potential for tourist scams that have occurred in the tourism industry. This research uses a bibliometric system. The data source comes from Scopus and SINTA indexed papers. The number of documents used is 110 papers. Based on the results of the study shows that there are 28 tourist scam schemes. Of the 28 schemes, price scams are the most common schemes in 48 papers. Other methods, such as corruption (38 documents), service scams (34 articles), fake products/souvenirs (23 articles), and food scams (30 papers). Meanwhile, in Indonesia, there were 17 tourist scam schemes found.